(untitled) (Current Horticulture, 2024)
The seed tubers of Colocasia (Colocasia esculenta L.) collected from different locations were treated with several bio-formulations, viz. Biofor PF-2, Biomonas, Bioveer and Biozin PTB at 5% concentration to evaluate their efficacy in protecting the seed tubers from rotting in storage. Biozin PTB was found to be the most effective with lowest incidence (8.84%) of rot among all bio-formulations. The seed tubers treated with Biozin PTB recorded highest reduction (80.94%) of rot incidence over the control.